Current practice and novel approaches in organ preservation - Ozgur, Ozge Sila; Namsrai, Bat-Erdene; Pruett, Timothy L.; Bischof, John C.; Toner, Mehmet; Finger, Erik B.; Uygun, Korkut (Frontiers in Transplantation, 2023)
Organ transplantation remains the only treatment option for patients with end-stage organ failure. The last decade has seen a flurry of activity in improving organ preservation technologies, which promise to increase utilization in a dramatic fashion. They also bring the promise of extending the preservation duration significantly, which opens the doors to sharing organs across local and international boundaries and transform the field. In this work, we review the recent literature on machine perfusion of livers across various protocols in development and clinical use, in the context of extending the preservation duration. We then review the next generation of technologies that have the potential to further extend the limits and open the door to banking organs, including supercooling, partial freezing, and nanowarming, and outline the opportunities arising in the field for researchers in the short and long term.